ANALISIS KEMAMPUAN LITERASI SAINS IPA PADA SISWA SMP DALAM MEMECAHKAN SOAL IPA - Zahro, Fatimatuz; Fauziah, An Nuril Maulida (PENSA E-JURNAL: PENDIDIKAN SAINS, 2025)
This study aims to analyze the ability of science literacy in junior high school students in solving science problems. The research method used in this study is qualitative descriptive. This research was carried out at SMP Negeri 16 Surabaya in the odd semester of the 2023/2024 academic year. The subjects in this study were grade IX students of SMP Negeri 16 Surabaya totaling 21 students. The population in this placement was all grade IX students of SMP Negeri 16 Surabaya who were then sampled using the Random Sampling technique. The results of this study showed that the ability of science literacy in junior high school students in solving science problems was low with the highest percentage of 57.1% on indicators explaining phenomena scientifically while the lowest percentage was 33.3% on indicators of evaluating and designing scientific investigations. The conclusion in this study is that the ability of science literacy in junior high school students in solving science problems is included in the low category. The low ability of science literacy is caused because students are less accustomed to involving science literacy skills in a learning where it is influenced by various factors